ПЕДАГОГИК ТЕХНОЛОГИЯЛАРДАН ФОЙДАЛАНИШ, МУСИҚА МАДАНИЯТИ ДАРСЛАРИ САМАРАДОРЛИГИНИНГ ТАЯНЧ ОМИЛИ СИФАТИДА - Одилов, А. (SCIENCE and SOCIETY, 2018)
The article is devoted to the description of some issues related to teaching "musical culture" at general educational schools and the ways of their solution. The article contains the methodological aspects of using pedagogical technologies at the lessons in the teaching of "musical culture".